2020
DOI: 10.1002/er.5158
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies on photovoltaic response of ultrathin CuSb(S/Se) 2 ternary compound semiconductors absorber‐based single junction solar cells

Abstract: Summary Copper‐based ternary CuSb(S/Se)2 compound semiconductors are showing promise for ultrathin photovoltaic devices. The high absorption coefficient of these semiconductors makes them suitable for very thin absorber, where maximum absorption can be achieved in a photovoltaic device with only nanometers thick CuSb(S/Se)2 based thin films. The device structure under consideration consists of AZO/i‐ZnO/n‐CdS/absorber layer/back contact, as the constituent material layers. The device structure is simulated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…The metal contact and hole transport material interface in practice exhibits ohmic or rectifying characteristics impeding the transport of holes. [ 64–66 ] Therefore, various back metal contacts with different work functions were studied, which can be employed as anode materials in the proposed Cs 2 SnI 6 perovskite solar cell. The potential energy barrier at the hole transport material and back metal contact interface is governed by the relation Vbbadbreak=Enormalgqgoodbreak+χgoodbreak−ϕm$$\begin{equation} {V}_{\rm{b}} = \frac{{{E}_{\rm{g}}}}{q} + \chi - {\phi }_{\rm{m}}\end{equation}$$where χ is the electron affinity and ϕ m is the metal work function.…”
Section: Optimization Of the Proposed Cs2sni6 Solar Cell: Results And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The metal contact and hole transport material interface in practice exhibits ohmic or rectifying characteristics impeding the transport of holes. [ 64–66 ] Therefore, various back metal contacts with different work functions were studied, which can be employed as anode materials in the proposed Cs 2 SnI 6 perovskite solar cell. The potential energy barrier at the hole transport material and back metal contact interface is governed by the relation Vbbadbreak=Enormalgqgoodbreak+χgoodbreak−ϕm$$\begin{equation} {V}_{\rm{b}} = \frac{{{E}_{\rm{g}}}}{q} + \chi - {\phi }_{\rm{m}}\end{equation}$$where χ is the electron affinity and ϕ m is the metal work function.…”
Section: Optimization Of the Proposed Cs2sni6 Solar Cell: Results And...mentioning
confidence: 99%
“…The metal contact and hole transport material interface in practice exhibits ohmic or rectifying characteristics impeding the transport of holes. [64][65][66] Therefore, various back metal con-tacts with different work functions were studied, which can be employed as anode materials in the proposed Cs 2 SnI 6 perovskite solar cell. The potential energy barrier at the hole transport material and back metal contact interface is governed by the relation…”
Section: Effect Of Metal Back Contactmentioning
confidence: 99%
“…It signifies that all the optimized solar cells have high resistance to the recombination of charge carriers than the initial solar cells. [ 81 ] More specifically, it can be concluded that the large W and high V b of the final solar cells have hastened the separation of charge carriers so that they are collected at the contacts before recombining, thereby contributing to enhanced solar cell performance. Therefore, the above‐discussed findings certainly disclose the dominant role of ZrS 2 properties on the efficient functioning of diverse emerging chalcogenide thin‐film solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…The copperzinc tin sulfoselenide (CZTSSe) was explored as a promising alternative material because it might fulfill the prerequisites for sufficient solar irradiation but still, the efficiency of PV devices is relatively low, despite more than a decade of painstaking researches [4]. The copper-based chalcogenide systems including CuSbS2 (Chalcostibite), Cu3SbS4 (Famatinite), Cu12Sb4S13 (Tetrahedrite), and Cu3SbS3 (Skinnerite) phases have been explored as they are interesting alternatives for CIGS thin-film solar cells due to their low-toxicity and earthabundant absorber components [3,[5][6][7][8][9][10][11][12][13]. The Cu-Sb-S system compounds are p-type semiconductors with optical band gap (Eg) ranging between 0.5 and 2.0 eV and a large absorption coefficient over 10 4 cm −1 at visible wavelengths, which shows a comparable efficiency (i.e., 22.9%) to that of CIGS and CZTSSe [14].…”
Section: Introductionmentioning
confidence: 99%